The The Impact of Adding Waste Pineapple Peel on the EOR Process to Increase Crude Oil Production (Rudarsko-geološko-naftni zbornik, 2023)
As the demand for energy continues to rise, it is still primarily met by fossil fuels and non-renewable energy sources. In addition, oil production, particularly in older fields, is declining. The enhanced oil recovery (EOR) method utilized in this study is surfactant injection with the addition of waste pineapple peel. The experiment was carried out in a controlled laboratory setting, using surfactant and brine solutions with salinities of 5,000 ppm and 12,000 ppm, respectively. The concentration range of alpha olefin sulfonate (AOS) surfactant employed ranged from 0.2% to 0.6% (2×10-6 m3 and to 0.6% from 1×10-3 m3). The solution was tested at two different temperatures, specifically 30°C and 60°C. The solution was tested with the addition of the pineapple peel and without pineapple peel. The density, viscosity, and interfacial tension of the two solutions were determined using laboratory measurements. The subsequent procedure involves the injection of the core sample in order to determine the oil recovery factor. The interfacial tension (IFT) values obtained were 17.5 mN/m in the absence of additives and 15.4 mN/m in the presence of additives derived from pineapple peel. The recovery factor for a solution with a salinity of 12,000 ppm and a concentration of 0.6% is determined to be 42.01%. Additionally, the recovery factor for a surfactant solution with the addition of pineapple peel is found to be 44.26%. Based on the findings of this study, the utilization of waste pineapple peel demonstrates a beneficial impact on the process of oil production.